Effects of partial soybean meal replacement with sunflower meal and non-starch polysaccharide degrading enzymes supplementation on broiler growth performance, nutrient digestibility, and gut morphology - Zeeshan Munawar; Saad Amjid; Faisal Ramzan; Azhar Rafique; Safdar Hassan; Urooj Anwar; Momna Mehmood; Umar Farooq; Muhammad Farooq Khalid; Riaz Mustafa; Muhammad Riaz; Muhammad Aziz ur Rahman; et al. (Veterinary World)
Background and Aim: Soybean meal (SBM) is the primary protein source in broiler diets; however, its high cost and import dependency necessitate alternative protein sources. Sunflower meal (SFM) is a viable alternative but contains high fiber and non-starch polysaccharides (NSPs), which can impair nutrient utilization. This study evaluated the effects of partially replacing SBM with SFM, with or without NSP degrading enzymes (NSPase) enzyme supplementation, on growth performance, nutrient digestibility, digesta viscosity, and gut morphology in broilers.